Mining characteristic clusters:a density estimation approach - Yi HAN; Bin-xing FANG; Yan JIA; Bin ZHOU; Wei-hong AN (Tongxin xuebao)
A hierarchical structure extraction approach based on clustering was proposed,and a density esti-mation based on topological structure was designed.By conducting the hierarchical aggregation on layers of hierarchical structure,the characteristic of clusters could be measured.The empirical study conducted on a large real data set indicates that the model and measures are interesting and meaningful,and the algorithms are effective and efficient in practice.